Actitudes del profesorado hacia la superdotación. Implicaciones para el desarrollo de programas de formación - Fernández, R.; Tourón, J.; Reyero, M. (FAISCA: Journal of High Abilities, 2002)
“Few would argue that the beliefs teachers hold influence their perceptions and judgement, which in turn, affect their behavior in the classroom, or that understanding the belief structures of teachers and teacher candidates is essential to improving their professional preparation and teaching practices” (Pajares, 1992). From this perspective, the analysis of attitudes and beliefs toward giftedness in student teacher’s seems to be of paramount importance as far as it would imply positive or negative behaviors in their future professions. This importance is even more evident in Spain where a lack of specific programs is the most common situation. This paper focuses on the perceptions and knowledge of a sample of student teacher’s towards gifted and talent students and the management of their educational needs in the classroom. The aim of the paper is to investigate not only the knowledge of the special educational needs of these students that the student teacher’s might have but also about their attitude with regard to the provision of adequate educational measures. After analyzing these aspects, we offer some suggestions about changes in the planning of the educational programs for these students.